1998
DOI: 10.1128/iai.66.3.974-979.1998
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins to Group A Streptococcal Surface Molecules Decrease Adherence to and Invasion of Human Pharyngeal Cells

Abstract: The M protein is one of the most important virulence factors of group A streptococci (Streptococcus pyogenes) and may play an important role in the first steps of streptococcal infection. Since acute pharyngitis is a frequently occurring infectious disease caused by these bacteria, we wished to know whether antibodies to the M protein or other surface components inhibit adherence and internalization of streptococci to pharyngeal cells. We investigated the role of whole human secretory immunoglobulin A (sIgA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…It is interesting to note that other investigators, employing a di¡erent cell culture model, also found a di¡erential e¡ect on adherence and internalization. For example, it was shown that anti-M6 IgG inhibited streptococcal internalization but not adherence [3]. Thus, it is likely that discrete cellular components might be required to mediate adherence and internalization.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that other investigators, employing a di¡erent cell culture model, also found a di¡erential e¡ect on adherence and internalization. For example, it was shown that anti-M6 IgG inhibited streptococcal internalization but not adherence [3]. Thus, it is likely that discrete cellular components might be required to mediate adherence and internalization.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms promoting GAS cell adherence and internalization appear to involve the expression of several virulence factors. Production of capsule material interferes simultaneously with both eukaryotic cell adherence and internalization (Darmstadt et al, 2000;Kawabata et al, 1999;Schrager et al, 1996), while bacterial surface proteins such as SDH, FBP54, and M proteins were found to contribute to adherence and internalization in a serotype or even strain-dependent manner (Courtney et al, 1996;Pancholi and Fischetti, 1997;Cue et al, 1998;Fluckiger et al, 1998;Berkower et al, 1999;Dombek et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The secretory IgA (sIgA) and IgG antibodies have been found to block S. pyogenes M protein-mediated adhesion and invasion of human pharyngeal cells [7]. We postulated that binding of Mig to IgA, IgG or anti-Mig serum might interfere with the bacterial interaction with the host cells since the Mig protein possesses similar antiphagocytic properties to the M protein.…”
Section: Mig-mediated Binding Properties Are Not Involved In S Dysgamentioning
confidence: 99%